Hybrid Endovascular Treatment of an Aortic Root and Thoracoabdominal Aneurysm in a High-Risk Patient With Marfan Syndrome. (May 2013) - Gelpi, Guido; Mazzaccaro, Daniela; Romagnoni, Claudia; Contino, Monica; Antona, Carlo
This report describes the hybrid endovascular treatment of an aortic root dilatation and a thoracoabdominal aneurysm in a high-risk patient with Marfan syndrome. A 50-year-old male, in hemodialysis for polycystic kidney and polycystic liver, was referred to our department for aortic root dilatation of 5 cm and a 6.3-cm thoracoabdominal aneurysm . He already underwent surgical repair of abdominal aortic aneurysm 10 years ago, complicated by pseudoaneurysm of the proximal anastomosis that had been treated in another center, with an endoprosthesis. The patient underwent aortic root replacement, aortic valve sparing operation, and rerouting of the superior mesenteric artery and celiac trunk to the ascending aorta. The thoracoabdominal aneurysm was excluded with an endoprosthesis few days after the surgical step. The 12-month computed tomography scan confirmed the complete exclusion of the thoracoabdominal aneurysm.